2013
DOI: 10.1177/1063426613478175
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety-Disordered Adolescents With and Without a Comorbid Depressive Disorder

Abstract: There is a high degree of comorbidity between anxiety and depressive disorders among treatment-seeking adolescents. Comorbid youth often present with greater diagnostic severity, worse social functioning, and more severe anxiety and depressive symptoms, compared with anxiety-disordered youth without depression. However, the degree to which these populations may differ in underlying affect and emotion regulation (ER) is largely unknown. This study compared 44 anxietydisordered adolescents (ages 12-18 years) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 52 publications
3
13
0
Order By: Relevance
“…We found that anxiety comorbidity in youngsters with lifetime depression was associated with dysfunctional ER, as children with comorbidity used maladaptive ER responses more frequently than non-comorbid peers. Our results are in line with findings from previous studies that showed more frequent use of maladaptive ER strategies in youths with comorbid depression and anxiety symptoms (11, 15, 36, 37, 47). It has been reported that the treatment of depression is more difficult in the presence of anxiety: comorbidity lengthens the duration of treatment and decreases the response to interventions (49, 50).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that anxiety comorbidity in youngsters with lifetime depression was associated with dysfunctional ER, as children with comorbidity used maladaptive ER responses more frequently than non-comorbid peers. Our results are in line with findings from previous studies that showed more frequent use of maladaptive ER strategies in youths with comorbid depression and anxiety symptoms (11, 15, 36, 37, 47). It has been reported that the treatment of depression is more difficult in the presence of anxiety: comorbidity lengthens the duration of treatment and decreases the response to interventions (49, 50).…”
Section: Discussionsupporting
confidence: 93%
“…In fact, there is scant information about how anxiety as a comorbid condition affects the habitual use of different ER strategies in depressed youngsters. Queen and Ehrenreich-May (47) found that adolescents with anxiety and depression had poorer emotional awareness, greater emotional suppression, greater reluctance to express negative emotions, and greater inhibition of sadness than are patients with anxiety disorder. Research by Burklund et al (48) in adults revealed altered ER in patients with comorbid social phobia and depression.…”
Section: Discussionmentioning
confidence: 99%
“…The ERQ-CA has been used with clinical and school samples of U.S. adolescents (Ben-Eliyahu & Linnenbrink-Garcia, 2015;Queen & Ehrenreich-May, 2014;Tsao, Jacob, Seidman, Lewis, & Zeltzer, 2014). However, no study (to the authors' knowledge) has verified the factor structure of the ERQ-CA using samples from U.S. adolescent population.…”
Section: Purpose Of Studymentioning
confidence: 99%
“…Estimates suggest that half of depressed individuals have a comorbid anxiety disorder (Kessler et al, 2003). Comorbidity is associated with greater symptom and diagnostic severity, and worse social functioning (Queen & Ehrenreich-May, 2014). It has been frequently reported that anxiety precedes depression (e.g., Cole, Peeke, Martin, Truglio, & Seroczynski, 1998; Keenan, Feng, Hipwell, & Klostermann, 2009; Avenevoli, Stolar, Li, Dierker, & Merikangas, 2001).…”
Section: Introductionmentioning
confidence: 99%